Comparison of skeletal stability after sagittal split ramus osteotomy among mono-cortical plate fixation, bi-cortical plate fixation, and hybrid fixation using absorbable plates and screws. Issue 2 (February 2017) - Ueki, Koichiro; Moroi, Akinori; Yoshizawa, Kunio; Hotta, Asami; Tsutsui, Takamitsu; Fukaya, Kenichi; Hiraide, Ryota; Takayama, Akihiro; Tsunoda, Tatsuta; Saito, Yuki
Abstract: Purpose: The purpose of this study was to examine skeletal stability and plate breakage after sagittal split ramus osteotomy (SSRO) with the mono-cortical plate fixation, bi-cortical plate fixation, and hybrid fixation techniques using absorbable plates and screws. Materials and methods: A total of 76 Japanese patients diagnosed with mandibular prognathism with and without maxillary deformity were divided into 3 groups randomly. A total of 28 patients underwent SSRO with mono-cortical plate fixation, 23 underwent SSRO with bi-cortical plate fixation, and 25 underwent SSRO with hybrid fixation. Skeletal stability and horizontal condylar angle were analyzed by axial, frontal, and lateral cephalograms from before the operation to 1 year postoperatively. Breakage of the plate and screws was observed by 3-dimensional computed tomography (3DCT) immediately after surgery and after 1 year. Results: Although there was a significant difference between the mono-cortical plate fixation group and hybrid fixation group regarding right MeAg in T1 (P = 0.0488) and occlusal plane in T1 (P = 0.0346), there were no significant differences between the groups for the other measurements in each time interval. In 2 cases, namely, 6 sides in the mono-cortical plate fixation group, breakage of the absorbable plate was found by 3DCT. However, there was no breakage in the bi-cortical plate fixation group and hybrid fixation group. Conclusion: This study results suggested that there were no significant differences in the postoperative skeletal stability among the 3 groups, and bi-cortical fixation as well as hybrid fixation was a reliable and useful method to prevent plate breakage even if an absorbable material was used.